The Role of 'Belladonna 200' in the Prevention of Japanese Encephalitis (JE) Virus Infection - Bandyopadhyay, Bhaswati; Das, Satadal; Sengupta, Milan; Saha, Chandan; Raveendar, Chinta; Chakravarty, Rathin; Khurana, Chaturbhuja Nayak Anil; Ray, Krishnangshu (IntechOpen, 2012)
None